2020
DOI: 10.1186/s40170-020-00217-6
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-induced lipid uptake and remodeling underpin ferroptosis hypersensitivity in prostate cancer

Abstract: Background Metabolic reprograming, non-mutational epigenetic changes, increased cell plasticity, and multidrug tolerance are early hallmarks of therapy resistance in cancer. In this temporary, therapy-tolerant state, cancer cells are highly sensitive to ferroptosis, a form of regulated cell death that is caused by oxidative stress through excess levels of iron-dependent peroxidation of polyunsaturated fatty acids (PUFA). However, mechanisms underpinning therapy-induced ferroptosis hypersensitiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 81 publications
(132 reference statements)
1
53
0
Order By: Relevance
“…Currently, it is not clear whether any final executioner proteins of ferroptosis exist, since the process essentially depends on the propagation of lipid peroxidation chain reactions and the ultimate failure of protective antioxidant mechanisms, progressively leading to irreparable membrane and organelle dysfunction. Importantly, induction of ferroptosis by inhibition of GPX4 and/or FSP1 is effective at killing multiple types of cancers in vitro and in vivo (Badgley et al 2020;Bersuker et al 2019;Doll et al 2019;Hangauer et al 2017;Tousignant et al 2020;Viswanathan et al 2017;Zhang et al 2019;Zou et al 2019). Thus, the stimulation of ferroptosis in tumors may offer new opportunities for effective cancer treatment.…”
Section: Lipid Droplets Lipid Peroxidation and Ferroptosis In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is not clear whether any final executioner proteins of ferroptosis exist, since the process essentially depends on the propagation of lipid peroxidation chain reactions and the ultimate failure of protective antioxidant mechanisms, progressively leading to irreparable membrane and organelle dysfunction. Importantly, induction of ferroptosis by inhibition of GPX4 and/or FSP1 is effective at killing multiple types of cancers in vitro and in vivo (Badgley et al 2020;Bersuker et al 2019;Doll et al 2019;Hangauer et al 2017;Tousignant et al 2020;Viswanathan et al 2017;Zhang et al 2019;Zou et al 2019). Thus, the stimulation of ferroptosis in tumors may offer new opportunities for effective cancer treatment.…”
Section: Lipid Droplets Lipid Peroxidation and Ferroptosis In Cancermentioning
confidence: 99%
“…Recent findings provide more support for the idea that lipid droplet breakdown regulates ferroptosis sensitivity. Several types of therapy-resistant cancer cells have been shown to be particularly sensitive to ferroptosis (Tousignant et al 2020;Viswanathan et al 2017). Namely, drug-resistant prostate cancer cells undergo an extensive metabolic reprogramming characterized by increased lipid uptake that drives lipid droplet accumulation and phospholipid remodeling.…”
Section: Lipid Droplets Lipid Peroxidation and Ferroptosis In Cancermentioning
confidence: 99%
“…It is a complex and vulnerable process affected by a variety of crosslinks among lipids, iron, amino acid metabolism and environmental stress (Galluzzi et al, 2018;Hirschhorn and Stockwell, 2019). Although the physiological role and function of ferroptosis in normal mammalian development have not been fully elucidated, emerging evidence has revealed that ferroptosis is implicated in a number neoplastic contexts, including breast cancer, renal cell carcinoma and prostate cancer (Lue et al, 2017;Hultsch et al, 2018;Tousignant et al, 2020). Recent studies have suggested that ferroptosis may play a role in tumor suppression through metabolic regulation and promotion of cell death (Gao et al, 2015;Jiang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 13 S -HODE, the major metabolite of 15-LOX-1 can interact with anti-apoptotic mediators such as B-cell lymphoma 2 (BCL2) and insulin-like growth factor receptor-1 (IGF-1R) which leads to inhibition of apoptotic signaling pathways in PC [ 59 61 ]. Additionally, recent studies demonstrated that 15-LOX-1 is one of the fundamental regulators in ferroptosis pathway [ 44 , 62 ], and is involved in PUFA oxidation and pro‐ferroptotic lipid peroxide generation [ 63 ]. In order to better evaluate the efficacy of anti-cancer agents, treatment strategy should also be assessed in animal experimental models [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%